PENEGAKAN HUKUM KESEHATAN TERHADAP KEGIATAN MALPRAKTEK DI INDONESIA - Kembaren, Novalina; Sembiring, Tamaulina (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
One of the most significant laws that Indonesian society is currently developing is health law. The development of health law serves as both a formality and a means of addressing the needs and demands of the expanding Indonesian society's legal system. This is why health law is becoming more and more important. The significance of Indonesian health law stems from the fact that the country's society has incorporated both health law and other laws. We can imagine that everything related to health would not function as needed if there were only health and no laws governing it. Health care providers and the general public who receive health services will have complete legal protection and legal certainty thanks to the existence of health law instruments. Malpractice cases have persisted in Indonesia up until this point. This is the area of focus where there is a great need for health law legislation. Case studies and literature reviews are the appropriate methods used in this research. The author will use a case study example to illustrate how health law is developing in Indonesia. While reading books and references, the author's study of literature aids in the composition of this piece. This paper's conclusion is that medical staff members' malpractice frequently harms patients and can have deadly results. Stricter enforcement of the Health Law regarding malpractice activities is required. This indicates that, based on the pertinent articles, it is clear that Malpractice Enforcement needs to be included in the legislation.